A comprehensive framework and literature review of supplier selection under different purchasing strategies. (May 2022) - Saputro, Thomy Eko; Figueira, Gonçalo; Almada-Lobo, Bernardo
Highlights: Framework provides guidance on approaching supplier selection in different settings. The problem should be formulated according to the type of item and production policy. The approach depends on criteria, decision scope, and decision environment. Risk, sustainability and new technologies should drive supplier selection research. Integration with logistics activities needs to be explored further. Abstract: Supplier selection has received substantial consideration in the literature since it is considered one of the key levers contributing to a firm's success. Selecting the right suppliers for different product items requires an appropriate problem framing and a suitable approach. Despite the vast literature on this topic, there is not a comprehensive framework underlying the supplier selection process that addresses those concerns. This paper formalizes a framework that provides guidance on how supplier selection should be formulated and approached for different types of items segmented in Kraljic's portfolio matrix and production policies. The framework derives from a thorough literature review, which explores the main dimensions in supplier selection, including sourcing strategy, decision scope and environment, selection criteria, and solution approaches. 326 papers, published from 2000 to 2021, were reviewed for said purpose. The results indicate that supplier selection regarding items with a high purchasing importance should lead to holistic selection criteria. In addition, items comprising a high complexity of supply and production activities should require integrated selection and different sources of uncertainty associated with decision scope and environment, respectively, to solve it, as well as hybrid approaches. There are still many research opportunities in the supplier selection area, particularly in the integrated selection problems and hybrid solution methods, as well as in the risk mitigation, sustainability goals, and new technology adoption.